The Role of HR Management, Innovation, and Entrepreneurial Traits on the Performance of Catfish MSMEs: A Case Study of Ngawi Regency - Puspita, Helda Jaya; Atmojo, Titin Andriani (ProBisnis : Jurnal Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the national economy, including the aquaculture subsector, such as catfish, which has great potential but whose performance has not yet been optimized. This research aims to analyze the influence of human resource management, innovation, and entrepreneurial characteristics on the performance of catfish farming MSMEs. The research was conducted in June 2025 in Ngawi Regency, East Java, involving the entire population of 55 MSME actors through the saturated sampling method. This study uses the variables of HR Management (X1), Innovation (X2), Entrepreneurial (X3), and MSME Performance (Y), which are analyzed using multiple linear regression after undergoing a series of classical assumption tests. The results show that simultaneously, the three variables significantly affect the performance of MSMEs, but partially, only the innovation variable has a significant impact on the performance of catfish farming MSMEs.